Investigation of the Antibacterial Properties of Janus Micromotors Catalytic Propelled by Manganese Dioxide and Hydrogen Peroxide to Reduce Bacterial Density - Cheng Yanfang; Liu Xiaolan; Rutkowski S. Sven; Badaraev A. D. Arsalan Dorzhievich; Kozelskaya A. I. Anna Ivanovna; Tverdokhlebov S. I. Sergei Ivanovich; Frueh J. C. Johannes Christoph (2024, 2024)
Title screen